2020
DOI: 10.1021/acs.jproteome.0c00439
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acid Diet and Upregulation of Lipoxin A4 Reduce the Inflammatory Response of Preeclampsia

Abstract: The aim of this study was to investigate the effects and mechanisms of polyunsaturated fatty acids (PUFAs) and lipoxin A4 (LXA4) on preeclampsia (PE). The LXA4 level was significantly reduced in PE rats. The PUFA diet upregulated the expressions of lipoxygenase 12 (LOX12) and lipoxygenase 15 (LOX15) and downregulated those of cyclooxygenase-2, tumor necrosis factor-α (TNF-α), and endoglin. Lipopolysaccharides could inhibit cell growth and cause inflammatory response, while the presence of PUFAs inhibited the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…It is rich in dietary fibre, vitamin C, vitamin E, folate, carotenoids and PUFA. Previous studies have shown that greater intake of the Mediterranean diet during pregnancy is associated with a reduced risk of GDM and PE (3235) . The Western diet, characterised by a greater intake of red meat, processed meat and fried foods, is rich in SFA, nitrosamines and other compounds related to oxidative stress and insulin resistance, which may increase the level of serum inflammatory markers (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…It is rich in dietary fibre, vitamin C, vitamin E, folate, carotenoids and PUFA. Previous studies have shown that greater intake of the Mediterranean diet during pregnancy is associated with a reduced risk of GDM and PE (3235) . The Western diet, characterised by a greater intake of red meat, processed meat and fried foods, is rich in SFA, nitrosamines and other compounds related to oxidative stress and insulin resistance, which may increase the level of serum inflammatory markers (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that LPS-induced LA metabolism disturbance is earlier than organ injury. Accumulated evidences indicated that USFA are substrates for the synthesis of multiple molecules that are active in inflammatory response [45][46][47][48]. Decreased Omega 6/Omega 3 FAs were proved to attenuate ethanol-induced liver injury [49].…”
Section: Discussionmentioning
confidence: 99%
“…As a representative chemical, the effects of NDGA on RSA are unclear; however, they are considered potentially relevant. NDGA regulates the expression of lipoxin A4 and inflammation levels, by affecting lipoxygenase, and influences the onset and development of preeclampsia 55 . This suggests that NDGA may play an important role in embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…NDGA regulates the expression of lipoxin A4 and inflammation levels, by affecting lipoxygenase, and influences the onset and development of preeclampsia. 55 This suggests that NDGA may play an important role in embryonic development. However, we only examined one chemical and may have overlooked some valuable active compounds.…”
Section: Drug Discovery and Molecular Dockingmentioning
confidence: 99%